In-vitro analysis of bioactivity, hemolysis, and mechanical properties of Zn substituted Calcium Zirconium silicate (baghdadite). Issue 11 (1st June 2021) - Yadav, Sushma; Shreyasi majumdar,; Ali, Akher; Krishnamurthy, Sairam; Singh, Preetam; Pyare, Ram
Abstract: In this work, for the first time, zinc substituted baghdadite (Ca3-x Znx ZrSi2 O9 ; x = 0, 0.1, 0.25 and, 0.5) ceramic was successfully prepared. A solid-state ceramic synthesis route was utilized to prepare a composite for biomedical applications. The incorporation of zinc oxide reduces the synthesis temperature. The properties of composites were presented in terms of Zinc oxide amount. In-vitro bioactivity and degradation results indicated lower degradation in comparison with pure baghdadite. The hemolysis rate was observed < 5 %. Spreading of MG-63 cells in a large number was found on the baghdadite in comparison with 0.5 mol % zinc oxide containing composite. The antibacterial activity of composites analyzed over E. Coli and S. Aureus bacterial strain using MTT assay. Results showed that anti-bacterial ability was more in zinc oxide containing composite and found more active towards E. Coli. However, the antibacterial activity was found less in baghdadite ceramic. Therefore considering the improved antibacterial activities, and controlled degradation, baghdadite/zinc oxide composite can be highly considered as a promising material for biomedical application. Highlights: Baghdadite/zinc oxide composite is prepared by the solid-state method. The incorporation of zinc oxide lowers the processing temperature. Zinc oxide in baghdadite reduces the degradation rate and improves the antibacterial activity. Composites are hemolytic.